The Effectiveness of Teacher Competition Analysis in Improving Insurance Literacy at National Level - Laratmase, Antonia Junianty; Kurniawan, Yohanes Jhony; Lie, Antonius Anton; Febrisutisyanto, Ady; Damara, Antonia Samantha; Robidi (Jurnal Manajemen Pendidikan, 2025)
Background Insurance literacy remains a critical component of financial education, particularly in developing nations where public understanding of insurance principles is often limited. Purpose This study aimed to determine the insurance literacy of teachers who had participated in the competition. Design/method/approach The method used was descriptive qualitative method with data collection techniques through questionnaires. Results The study results were: (1). The teacher insurance knowledge level was already at a high level, well literate, with a score of 240 the interval of 160-240. This meant that the respondents had already understood the basic concepts of risk and insurance well. (2). The insurance skills level was at the level of quite literate with a score of 235. This meant that the respondents were skilled enough in managing risk and insurance. Contribution/value the respondents had already understood the basic concepts of risk and the concept of insurance well, but they were still not quite skilled in managing the risk and insurance; respondents were also still hesitant about insurance and insurance capabilities.